Evaluation of treatment outcome using the Patient Specific Functional Scale in knee osteoarthritis patients undergoing multidisciplinary rehabilitation. Issue 4 (December 2020) - Moore, H.E.; Corning, W.L.; van der Esch, M.; Roorda, L.D.; Dekker, J.; Groot, J.; Wijbenga, M.H.; Lems, W.F.; van der Leeden, M.
Summary: Objective: First, to make an inventory of activity limitations commonly reported by knee osteoarthritis (OA) patients undergoing multidisciplinary rehabilitation. Second, to evaluate treatment outcome using the Patient Specific Functional Scale (PSFS) and compare it to the Western Ontario and McMasters Universities Osteoarthritis Index physical function subscale (WOMAC-pf). Design: An observational study with assessments before and immediately after multidisciplinary rehabilitation. Five hundred and thirteen patients used the PSFS, a patient-reported tool to identify activity limitations and score the patient's ability to perform the activity on an 11-point Numeric Rating Scale (NRS), to report three activities in which they were limited. Frequencies and percentages of their highest-prioritized activity were calculated and categorized according to the International Classification of Functioning, Disability, and Health (ICF). Paired-samples T-tests were used to analyze the change in ability to perform the activities. Effect sizes of PSFS and WOMAC-pf were compared. Results: Most patients indicated limitations in walking, walking up/down stairs, prolonged standing, and standing up from a chair. Following these common activities, 26 different activities were identified. The majority of these highest-prioritized activities fell under the first-level ICF category of Mobility. The ability to perform all activities significantly improved after treatment. Effect sizes ranged between 0.60 and 0.97 and were greater than the effect size of the WOMAC-pf (0.41). Conclusion: Knee OA patients who undergo multidisciplinary rehabilitation exhibit improvements in performing daily activities. The PSFS is a valuable tool to evaluate patient-specific activity limitations and seems to capture improvements in activity limitations beyond the WOMAC-pf.